Differential effects of FODMAPs (Fermentable Oligo-, Di-, Mono-Saccharides and Polyols) on small and large intestinal contents in healthy subjects shown by MRI - Murray, Kathryn; Wilkinson-Smith, Victoria; Hoad, Caroline; Costigan, Carolyn; Cox, Eleanor; Lam, Ching; Marciani, Luca; Gowland, Penny A.; Spiller, Robin C. (Nature Publishing Group, 2013)
OBJECTIVES: The objective of this study was to investigate whether ingestion of fructose and fructans (such as inulin) can exacerbate irritable bowel syndrome (IBS) symptoms. The aim was to better understand the origin of these symptoms by magnetic resonance imaging (MRI) of the gut. METHODS: A total of 16 healthy volunteers participated in a four-way, randomized, single-blind, crossover study in which they consumed 500 ml of water containing 40 g of either glucose, fructose, inulin, or a 1:1 mixture of 40 g glucose and 40 g fructose. MRI scans were performed hourly for 5 h, assessing the volume of gastric contents, small bowel water content (SBWC), and colonic gas. Breath hydrogen (H 2) was measured and symptoms recorded after each scan. RESULTS: Data are reported as mean (s.d.) (95 % CI) when normally distributed and median (range) when not. Fructose increased area under the curve (AUC) from 0 – 5 h of SBWC to 71 (23) l / min, signiﬁcantly greater than for glucose at 36 (11 – 132) l / min ( P < 0.001), whereas AUC SBWC after inulin, 33 (17 – 106) l / min, was no different from that after glucose. Adding glucose to fructose decreased AUC SBWC to 55 (28) l / min ( P = 0.08) vs. fructose. Inulin substantially increased AUC colonic gas to 33 (20) l / min, signiﬁ cantly greater than glucose and glucose + fructose (both P < 0.05). Breath H 2 rose more with inulin than with fructose. Glucose when combined with fructose signiﬁ cantly reduced breath H 2 by 7,700 (3,121 – 12,300) p.p.m. / min relative to fructose alone ( P < 0.01, n = 13). CONCLUSIONS: Fructose but not inulin distends the small bowel with water. Adding glucose to fructose reduces the effect of fructose on SBWC and breath hydrogen. Inulin distends the colon with gas more than fructose, but causes few symptoms in healthy volunteers.